2012
DOI: 10.7314/apjcp.2012.13.5.1935
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Treatment Outcomes in 93 Patients with Uterine Sarcoma from 4 Centers in Turkey

Abstract: Median overall survival (OS) was 56 months (95% CI, 22.5-89.5 months), and OS after 1, 2, 5 years was 84.7%, 78%, 49.4% respectively. Multivariate analysis showed that age ≥60 years and high grade tumor were significantly associated with poor OS and RFS; patients administered adjuvant treatment with sequential chemotherapy and radiotherapy had longer RFS time. Among patients with leiomyosarcoma, in addition to age and grade, adjuvant treatment with sequential chemotherapy and radiotherapy after surgery had sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 36 publications
3
24
4
Order By: Relevance
“…Our data were consistent with Benito et al study which found CS in 48% and LMS in 22% (Benito et al, 2009). Contrast with other studies in Thailand, most common type are LMS .Other previous studies reported different findings, with similar frequency of CS and LMS (Kelly and Craighead, 2005;Koivisto et al, 2008;Park et al, 2008;Durnali et al, 2012). The small number of cases in each study might have exaggerated the different proportion of each uterine sarcoma type.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Our data were consistent with Benito et al study which found CS in 48% and LMS in 22% (Benito et al, 2009). Contrast with other studies in Thailand, most common type are LMS .Other previous studies reported different findings, with similar frequency of CS and LMS (Kelly and Craighead, 2005;Koivisto et al, 2008;Park et al, 2008;Durnali et al, 2012). The small number of cases in each study might have exaggerated the different proportion of each uterine sarcoma type.…”
Section: Discussioncontrasting
confidence: 50%
“…Regarding stage of disease, nearly 60% of our patients had early stage. This was comparatively low compared to other studies which reported 60%-76% ( Koivisto et al, 2008;Park et al, 2008;Benito et al, 2009;Durnali et al, 2012). The differences might lie on the extent of operative procedure especially lymph node surgical evaluation and the proportion of the type of sarcoma.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Adjuvant therapy was chemotherapy in 20 patients, radiotherapy in 9, and sequential chemotherapy plus radiotherapy in 12. They also performed subgroup analyses for the LMS cohort and found that adjuvant sequential chemotherapy plus radiotherapy showed a significantly positive effect on OS (19).…”
Section: Discussionmentioning
confidence: 99%